Penguatan Kemampuan Guru Dalam Mengembangkan Perangkat Pembelajaran Tematik Berbasis Student Centre Learning (SCL) di SDN Petemon IX Surabaya - Endang Suprapti; Sujinah Sujinah; Wiwi Wikanta; Suher Suher (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2017)
Current elementary education, the first decade of the 21st century, is faced with a global challenge where the pattern of people's lives is changing very rapidly, fueled mainly by the development of information technology and global challenges. Devotion to the community is offered to solve the problems faced by a group of elementary school teachers Petemon, Sawahan, Surabaya. Seeing the problem of partner of implementation method offered in dedication to solve the problems faced by teacher group of SDN Patemon IX are (1) Training of applying of learning model of Student Center Learning on Mathematics, Biology and Bahasa Indonesia subjects to SDN Patemon IX, (2) Evaluation of training result of SCL instructional model implementation in Mathematics, Biology and Bahasa Indonesia subjects to teachers of SDN Patemon IX, (3) Review and Assistance in the preparation of fourth-, fourth and fourth-grade thematic RPP, (4) Assistance in Implementation of RPP in Thematic Class IV, V and VI learning, (5) Evaluation of compilation result and Assistance of implementation of RPP in thematic learning of class IV, V and VI. Proposal method to solve the problem that has been formulated is divided into three stages: preparation, implementation and reflection. Strengthening teacher's ability in developing thematic learning tool based on Student Center Learning (SCL) at SDN PATEMON IX Surabaya, get very positive response shown from Reflection result at end of mentoring. To design a mentoring program that suits the training needs some things are needed in designing the mentoring.